Bioecology and prospects of essential oil and medicinal plants cultivation in Surkhandarya region - Begmatov Abdusamat; Ganieva Gulirukhsor (Zien Journals, 2021)
It is emphasized that the role of natural remedies in the treatment of some diseases is invaluable in the process of medical reform. Therefore, large-scale measures are being taken in our country on the basis of state programs to increase the number of medicinal plants and organize their processing said President Shavkat Mirziyoyev. At the suggestion of Mirziyoyev, tasks are being given to establish plantations of medicinal plants in certain regions of the country and process them. During the visit of the President to the Surkhandarya region, these proposals on the effective use of existing opportunities in the region, especially in the desert and mountainous areas, will open a new stage in the work on the cultivation of medicinal plants.
Keywords: Medicinal plants; lavender; stevia; medicinal valerian